THE FACTORS AFFECTING EFFICIENCY OF CRUDE PALM OIL IN INDONESIA PALM OIL INDUSTRY - Yuli Eni; Christy Agustina; Metta Merlinna; Risya Bella; Roberto M. Arguelles; Sheryl Satorre-Estella (Bina Nusantara University, 2020)
This research aim is to determine the factors affecting efficiency of crude palm oil (CPO) in Indonesia by using simpleregression (T-partial) and multiple regression (F-simultaneous) analysisthrough EViewssoftware. The results of this study indicate that partially is the independent variables that affecting Crude Palm Oil (Y) with a T-Statistic value greater than T table (1.65) are the total concession (7.214855), issued capital(2.087724), total investment (6.538604) andtotal employees (5.167861) with an alpha value of 0.05. While simultaneously,the independent variables that affecting the dependent variable are total concession, authorized capital, issued capital, paid up capital, total investment, total employees with F-statistic value of 16,65554, F table value of 1.94 with alpha value of 0.05 . Therefore, the palm oil industry in Indonesia can improveefficiency and production through maximum use of total concession inputs, issuedcapital, total investment and total employees.